Differing bodyminds: Cripping choreography. Issue 2 (22nd December 2022) - Van Goidsenhoven, Leni; Rutgeerts, Jonas; Sandahl, Carrie
In this position paper we start to articulate what crip theory can open up for choreography and dance. Crip theory is a critical perspective that analyses, exposes and critiques systems of normalcy in representation and social practices as well as a framework for imagining alternatives based on disabled ways of being in the world. The term crip, short-hand for the derogatory term 'cripple', is a re-appropriation by disabled individuals and communities, an act of pride, a demand for inclusion in mainstream life, and, paradoxically, a defiant occupation of the margins. 'Crip theory and choreography' was also the topic of a symposium and doctoral school we organized in Belgium in the spring of 2022. The aim of that event was to adopt the contemporary performing arts as a realm for our theorizing in embodied and experiential forms of knowledge-making in research and art practice. Over the course of the symposium and doctoral school, we explored how 'crip dance' might produce difference not as a divergence from the norm, but rather as a constant process of differing that opens up multiple ways of relating to body, mind and movement. Inspired by our explorations and encounters during the event, we are guest editing a Special Issue of Choreographic Practices . What we would like to contribute to conversations already happening in this journal is extended exploration of how disability studies and its unruly offspring, crip theory, not only critique the ableist structures that define mainstream dance, but offer alternative possibilities created by non-normative bodyminds.